How decision-styles and cultural orientation influence entrepreneurial and social entrepreneurial intentions: A cross-cultural comparison - Brandon William Soltwisch; Daniela Dimitrov; Jana Hojnik (Frontiers in Psychology, 2023)
This paper investigates how maximizing or satisficing decision styles and cultural orientation influence individuals’ entrepreneurial intentions. With a growing interest in social entrepreneurship, it also measures if these factors encourage individuals to start ventures with a social mission. Two studies are conducted to compare students’ entrepreneurial intentions in the U.S. and in Slovenia. By identifying that maximizing decision styles are associated with an individualistic cultural orientation in both the U.S. and Slovenia, the current study indicates that the maximizing – individualism connection spans national and cultural boundaries. In the U.S. sample, individualism mediated the relationship between decision styles and entrepreneurial intentions, suggesting that in individualistic cultures, such as the U.S., those who maximize their decision efforts and apply a more individualistic cultural perspective are especially inclined to pursue entrepreneurial opportunities. Similarly, individualism mediated the relationship between maximizing and social entrepreneurial intentions in the U.S. sample; suggesting that maximizers who are less individualistic may be more likely to start social enterprises over traditional ventures. Among the Slovenian sample, there was a marginally significant relationship between maximizing and entrepreneurial intentions and no relationship with social entrepreneurial intentions. These cross-cultural differences are discussed in relation to the economic and social conditions in each country.